The Implementation of Maqasid Shariah in Economic Studies - Maripatul Uula, Mimma; Darwis Harahap (Journal of Islamic Economics Literatures, 2023)
This study aims to see the development of research "Maqashid Sharia on Economics” around the world and research plans that can be carried out based on journals published on that theme. This study used a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Maqashid Sharia on Economics” which comes from the Scopus database with a total of 118 journal articles. The results of the study found that in the author mapping bibliometrics the author published the most research with the theme "Maqashid Sharia on Economicsis Choudhury M.A. Furthermore, based on the bibliometric keyword mapping, there are 6 clusters that can become research lines with topics related to Sustainable Economic Development and Maqashid Syariah, The COVID-19 pandemic in Islamic Finance and Maqashid Syariah, Environmental Protection in Perspective of Islamic Law and Maqashid Syariah, Financing in Islamic Banking and Maqashid Syariah, Islamic Economic System and Maqashid Syariah, dan SDGs and Maqashid Syariah and for the most used words are finance, Islamic finance, maqashid sharia, bank, Islamic bank, and Islamic law.